The Aryan Jesus : Christian theologians and the Bible in Nazi Germany - Heschel, Susannah 1952- (Princeton Univ. Press, 2008)
Introduction: Theology and race -- Draining Jesus of Jewishness -- The Institute for the Study and Eradication of Jewish Influence on German Church Life, 1939 to 1942 -- Projects of the Institute -- The making of Nazi theologians -- The Faculty of Theology at the University of Jena -- The postwar years -- Conclusion: Crucified or resurrected : Institute theology in postwar Germany